2015
DOI: 10.3168/jds.2014-8552
|View full text |Cite
|
Sign up to set email alerts
|

Enteric methane production, rumen volatile fatty acid concentrations, and milk fatty acid composition in lactating Holstein-Friesian cows fed grass silage- or corn silage-based diets

Abstract: The objective of this study was to determine the effects of replacing grass silage (GS) with corn silage (CS) in dairy cow diets on enteric methane (CH4) production, rumen volatile fatty acid concentrations, and milk fatty acid (FA) composition. A completely randomized block design experiment was conducted with 32 multiparous lactating Holstein-Friesian cows. Four dietary treatments were used, all having a roughage-to-concentrate ratio of 80:20 based on dry matter (DM). The roughage consisted of either 100% GS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
114
3
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 113 publications
(148 citation statements)
references
References 40 publications
18
114
3
4
Order By: Relevance
“…These results can be explained by the higher quality of corn plants, with more appropriate DM contents than other silage grasses. Importantly, the results obtained by Van Gastelen et al (2015) demonstrate the potential of Brazilian corn silage to simultaneously increase animal efficiency and reduce greenhouse gasses, the latter being a major objective of the 2015 Paris Climate Conference (COP 21). Therefore, it is crucial that Brazil allocate more financial resources to research on the production, handling, and use of conserved forage (silage and hay), as well as on the potential beneficial and deleterious environmental impacts of such processes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results can be explained by the higher quality of corn plants, with more appropriate DM contents than other silage grasses. Importantly, the results obtained by Van Gastelen et al (2015) demonstrate the potential of Brazilian corn silage to simultaneously increase animal efficiency and reduce greenhouse gasses, the latter being a major objective of the 2015 Paris Climate Conference (COP 21). Therefore, it is crucial that Brazil allocate more financial resources to research on the production, handling, and use of conserved forage (silage and hay), as well as on the potential beneficial and deleterious environmental impacts of such processes.…”
Section: Resultsmentioning
confidence: 99%
“…Van Gastelen et al (2015) analyzed the replacement of corn silage with starchless grass silage on ruminal volatile fatty acid concentration, pH, and methane (CH 4 ) mitigation. The authors reported that increasing proportions of corn silage resulted in linear decreases in NDF intake (P < 0.001) and CP (P = 0.002) and linearly increases in starch intake (P < 0.001), whereas CH 4 emission decreased in a quadratic manner (P < 0.001) and decreased linearly (P = 0.010) when expressed as g CH 4 kg -1 DM intake.…”
Section: Resultsmentioning
confidence: 99%
“…Each block of six cows was completed within two consecutive periods; cows and treatments were randomly distributed to the CRC and periods. A detailed description of the CRC design and gas measurements was reported by van Gastelen et al (2015). Briefly, in each CRC (volume 35 m 3 ) relative humidity was maintained at 70% and temperature at 16°C.…”
Section: Grassland Managementmentioning
confidence: 99%
“…For example, at the animal level, replacing grass or grass silage with corn silage in the diet is a valuable strategy with an immediate effect in reducing GHG emissions (e.g., Beauchemin et al, 2008;Van Gastelen et al, 2015). However, at the farm and chain level, the strategy is not applicable for farms that cannot further reduce their grassland surface because of compliance with the European Union (EU) derogation regulation.…”
Section: Applications Of Proxies To Cattle Managementmentioning
confidence: 99%